Heterodox macro after the crisis - Peter Skott (University of Massachusetts, Department of Economics, 2011)
Macroeconomics is in crisis and this creates openings for alternative perspectives. The dominant heterodox traditions, however, have shortcomings that need to be addressed, both to improve our understanding of the real world and to take advantage of the opportunities offered by the irrelevance of most mainstream macro. This paper discusses three examples of areas that need attention: (i) investment functions (where popular specifications lack behavioral and empirical support), (ii) income distribution (where key developments have received little attention) and (iii) the relation between income inequality and financial markets (where extensions of existing models may help explain financial instability).
Keywords: E12; E21; E22; 330; investment; earnings inequality; financial instability